Optimizing the use of cesarean section in Argentina: design and methodology of a formative research for the development of interventions - Ramos, Silvina (2021)
Background: While cesarean section is an essential life-saving strategy for women and newborns, its current overuse constitutes a global problem. The aim of this formative research is to collect information from hospitals, health professionals and women regarding the use of cesarean section in Argentina. This article describes the methodology of the study, the characteristics of the hospitals and the profile of the participants. Methods: This formative research is a mixed-method study that will be conducted in seven provinces of Argentina. The eligibility criteria for the hospitals are (a) use of the Perinatal Information System, (b) cesarean section rate higher than 27% in 2016, (c) ≥ 1000 deliveries per year. Quantitative and qualitative research techniques will be used for data collection and analysis. The main inquiry points are the determining factors for the use of cesarean section, the potential interventions to optimize the use of cesarean section and, in the case of women, their preferred type of delivery. Discussion: It is expected that the findings will provide a situation diagnosis to help a context-sensitive implementation of the interventions recommended by the World Health Organization to optimize cesarean section use. Trial registration IS002316 Plain English Summary: Cesarean section is an essential medical tool for mothers and their children, but nowadays its overuse is a problem worldwide. Our purpose is to get information from hospitals, health professionals and women about how cesarean section is used in Argentina. In this protocol we describe how we will carry out the study and the characteristics of the hospitals and participants. We will implement this study in seven provinces of Argentina, in hospitals that have more than 1,000 births each year, had a cesarean section rate higher than 27% in 2016 and use the Perinatal Information System. We will gather information using forms, surveys and interviews. We want to identify the factors that decide the use of a cesarean section, the potential interventions that can improve the use of cesarean section and, in the case of women, the type of delivery they prefer. We expect that this study will give us a diagnosis of how cesarean section is used in Argentina, and that this will help to apply the interventions that the World Health Organization recommends to optimize the use of cesarean section in our specific context.